Efficacy of Tranexamic Acid for Reduction of Postoperative Seroma Formation after Ventral Hernioplasty (Medical Forum Monthly, 2021)
Objective: To assess the effectiveness of tranexamic acid for reduction of postoperative seroma formation in patients undergoing ventral hernioplasty.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at the department of surgery District Headquarter Teaching Hospital Sargodha for duration of one year from September 2019 to August 2020.Materials and Methods: One hindered patients of both genders with ages 20 to 65 years undergoing ventral hernioplasty were enrolled. After written consent, patients were registered for the comprehensive demographic age, sex and body mass index. Patients were categorized in to two equal groups. Group I contains 50 patients and received tranexamic acid 1gm postoperatively while group II didn’t received tranexamic acid. Drain output at 1stand 5th postoperative day was measured. Duration of drain was recorded and compare between both groups. Data was analyzed by SPSS 27.0.Results: There were 14(28%) males and 36 (72%) females in group I while in group II 32 (64%) patients were females and 18 (36%) males. Mean body mass index of patients in Group I was 24.36±2.78 kg/m2 while in Group II mean BMI was 24.72 ± 3.05 kg/m2.A significant short time of drainage was found in Group I 4.96±0.85 days as compared to Group II 6.88±1.56 days (p-value <0.05). In Group I and II 5 (10%) and 8 (16%) patients developed seroma, no significant difference was observed with p-value >0.05.Conclusion: The use of tranexamic acid for prevention of postoperative seroma formation in patientsundergoing ventral hernioplasty was effective with less interval of time for removal of drain.